1 - The Impact of Non-formal Education on Skills and Knowledge of Community Development Workers: A Case Study - Kotzé Derica Alba (Africa Development, 2021)
The ultimate route to address the needs of the poor is through a community development process with projects as the main vehicle. The main role player to facilitate this process is the community development worker. This article focuses firstly on the role and importance of non-formal education in community development and, secondly, on the impact of non-formal education and training on the knowledge and skills of community development workers responsible for the facilitation of projects. The article is based on an evaluation of a non- formal education programme that was developed to enhance the knowledge and skills of community development workers involved in the planning and execution of community-based development projects.